ANALYSIS OF STUDENTS' SCIENTIFIC LITERACY ABILITIES ON PHASE E GLOBAL WARMING MATERIALS - Amalia, Yunalisa (Universitas Negeri Padang, 2024)
In the modern era, education provides graduates with diverse skills, including the ability to understand and apply scientific concepts. Scientific literacy entails utilizing scientific knowledge, recognizing inquiries, making informed conclusions supported by evidence, comprehending the environment and its human-induced alterations, and making informed choices. In assessing scientific literacy abilities, there are four aspects, namely content, context, abilities and attitudes. The aim of this capability is to provide a strong scientific foundation in discussing global issues. This research aims to analyze students' scientific literacy abilities in learning physics material on Global Warming Phase E. This type of research uses a quantitative descriptive approach with a survey method in the form of questions as an instrument for collecting data. The results of the data obtained and after analyzing the four aspects of scientific literacy, students experienced literacy misconceptions. The percentage obtained for the misconception category is very high in the range of 78 – 82%, while for the literacy understanding category the percentage is low compared to the other two categories although there is no significant difference with the not understanding literacy category. The cause of students experiencing misconceptions about the questions given is caused by several factors. The influence of misconceptions on students' scientific literacy abilities is quite large. Overall, it can be said that the scientific literacy abilities of students at SMAN 5 Pariaman who understand literacy are in the very low category.